(Nuclear) Change of Plans: What Explains Nuclear Reversals?. Issue 3 (26th May 2016) - Mattiacci, Eleonora; Jones, Benjamin T.
ABSTRACT: What explains a state's decision to give up its nuclear weapons program? While instances of nuclear reversal figure prominently in international politics, evidence in the literature has been largely piecemeal. We offer a novel conceptualization of the proliferation process as nonlinear, potentially including instances of reversal, as well as pursuit of a nuclear program and acquisition of nuclear weapons. Employing this theoretical framework, we consider states' cost-benefit calculations in each phase of the proliferation process, and we test our theory using a multistate model. Two counterintuitive findings emerge from this framework. First, nuclear latency increases the likelihood of pursuit and acquisition but also increases the likelihood of reversal by reducing the costs of restarting a program in the future. Second, the nonproliferation regime discourages states without a nuclear program from pursuing and acquiring nuclear weapons while at the same time making states with nuclear programs less likely to reverse course.